2018
DOI: 10.18203/issn.2454-5929.ijohns20180016
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic membrane perforation: correlation of hearing loss with its site and size

Abstract: <p class="abstract"><strong>Background:</strong> The objectives of the study were <span lang="EN-IN">correlation of hearing loss with size and site of tympanic membrane perforation. </span></p><p class="abstract"><strong>Methods:</strong> <span lang="EN-IN">A cross-sectional prospective study of 100 patients of both sex and age between 11-60 years with perforated tympanic membrane was conducted in the department of Otorhinolaryngology (ENT). Size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
5
5
0
2
Order By: Relevance
“…8 The most common symptom in our study was otorrhea with hearing loss in 64%, followed by otorrhea only in 19%, otorrhea with otalgia in 7% and tinnitus with otalgia in 6% patients. Gulati et al 15 in their study reported that main symptoms was hearing loss and otorrhea similar to our findings whereas, Sood et al observed otorrhea in 98%, consistent with results of Kumar et al and Nahata et al 7,8,16 All the ears included in our study had a mild degree of hearing loss. One possible reason may be the exclusion of unsafe ears and ears with ossicular and mastoid pathology from the study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…8 The most common symptom in our study was otorrhea with hearing loss in 64%, followed by otorrhea only in 19%, otorrhea with otalgia in 7% and tinnitus with otalgia in 6% patients. Gulati et al 15 in their study reported that main symptoms was hearing loss and otorrhea similar to our findings whereas, Sood et al observed otorrhea in 98%, consistent with results of Kumar et al and Nahata et al 7,8,16 All the ears included in our study had a mild degree of hearing loss. One possible reason may be the exclusion of unsafe ears and ears with ossicular and mastoid pathology from the study.…”
Section: Discussionsupporting
confidence: 92%
“…The highest number of ears was seen in group III (72%), while the lowest number was seen in group I (3%). This was consistent with Nahata et al who found that group III was most commonly involved (43%), while group I was most commonly involved (47%) in the study of Pannu et al and Sood et al 7,8,12 However, John et al in his study, observed that group II had highest number of perforations (62%). 17 In our study, we did not find any significant correlation between duration of symptoms and the degree of hearing loss.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar observations have been reported in the earlier literature as well. Sood et al [25] reported that 79% of patients were less than 40 years of age in their study. While as Ediale et al [26], Bhusal et al [27], and Rana et.…”
Section: Discussionmentioning
confidence: 86%